Long‐Term Firocoxib Use in Horses - Iuri Buzelato Carli; Langdon Fielding (Journal of Veterinary Internal Medicine)
ABSTRACT Background Many horses receive firocoxib over multiple years, and studies evaluating hematologic and biochemical values in these animals are lacking. Objective To describe the hematologic and biochemical values of horses receiving long‐term firocoxib. Animals A total of 79 horses receiving long‐term firocoxib and 153 horses not receiving long‐term firocoxib and not presenting for a specific medical problem. Methods Retrospective study comparing horses receiving firocoxib (F group) and no firocoxib (NF group). Signalment, hematologic, and biochemical values were compared between the two groups. Simple linear regression was used to evaluate the relationship between the duration of firocoxib administration and specific laboratory variables. Results Horses receiving long‐term firocoxib (F) were 19 (5–33) years as compared to 15 (1–33) years for the NF group (p < 0.0001). The most common reason for receiving firocoxib was osteoarthritis in 44/79 (56%) of the animals in the F group. Horses in the F group had a total protein concentration of 6.6 (5.8–8.0) g/dL as compared to 6.5 (5.1–8) g/dL in the NF group (p = 0.03). The sodium concentration for F horses was 139 (133–143) mmol/L as compared to 138 (129–145) mmol/L for NF horses (p = 0.01). Total white blood cell count was 6.11 (2.82–14.36) 103 cells/uL in the F group as compared to 6.46 (3.04–14.71) 103 cells/uL in the NF group (p = 0.03). None of the laboratory variables were associated with the duration of firocoxib administration. Conclusions and Clinical Importance Many horses receive firocoxib for multiple years, and equine practitioners should be aware that expected changes in laboratory values are minimal.